Effects of Aspiration Prevention Surgery on the Dynamics of the Pharynx and Upper Esophageal Sphincter. Issue 4 (October 2021) - Ueha, Rumi; Sato, Taku; Goto, Takao; Koyama, Misaki; Yamauchi, Akihito; Mizukami, Aiko; Yamasoba, Tatsuya
Objective: Oral intake after aspiration prevention surgery (APS) is influenced by postoperative pharyngeal pressure and the dynamics of the upper esophageal sphincter (UES). We examined the effects of less invasive APS combined with UES relaxation techniques (laryngeal closure with cricopharyngeal myotomy [LC-CPM] and central-part laryngectomy [CPL]) on pharyngeal pressure and UES dynamics. Study Design: Retrospective, observational study. Setting: Single center. Methods: We assessed the high-resolution pharyngeal manometric parameters of patients who underwent APS from 2018 to 2020. Then, we compared the effects of bilateral cricopharyngeal myotomy (combined with LC: LC-CPM group) and total cricoidectomy (CPL group) on both pharyngeal pressure and UES dynamics pre- and postoperatively. Results: Eighteen patients (median age, 68 years; 17 men [94%]) were enrolled. Primary diseases associated with severe aspiration were neuromuscular disorders in 13, stroke in 3, and others in 2 patients. Pharyngeal swallowing pressure did not significantly change before and after APS. UES resting pressure and UES relaxation duration were significantly reduced ( P < .001) and prolonged ( P < .001), respectively, after APS. Only the CPL group (8 patients: median 62 years, all men) showed an increase in the velopharyngeal closure integral after APS ( P < .05). More prolonged UES relaxation duration was recognized postoperatively in the CPL group ( P < .01) than in the LC-CPM group. Conclusion: Less invasive APS minimally affects pharyngeal swallowing pressure, decreases UES resting pressure, and prolongs UES relaxation duration. CPL may be more effective for postoperative UES relaxation in patients with a short UES relaxation time.